Belonging to the Russian-speaking community: the socio-political aspect of self-identification of a citizen of Ukraine - Zhornova, Olga Ilyinivna (Psychological Prospects Journal, 2013)
The article outlines the reasons for proving an ordinary citizen of his own belonging to the Russian-speaking community. The essence of socio-psychological optimization of the consequences of identification with the Russian-speaking community is determined. Described psychological and correctional means of optimizing the process of integration of the Russian-speaking community.